2005
DOI: 10.1097/01.hjh.0000183119.92455.a7
|View full text |Cite
|
Sign up to set email alerts
|

C-344T polymorphism of the aldosterone synthase gene and blood pressure in the elderly: a population-based study

Abstract: These data support the concept that the C-344T polymorphism plays a role in controlling systolic blood pressure and the age-related increase in systolic blood pressure in response to age and to body fat, possibly through differences in modulation of aldosterone synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
46
1
3

Year Published

2007
2007
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 46 publications
2
46
1
3
Order By: Relevance
“…[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] In addition, our results were not consistent with previous reports indicating that BP elevation was sensitive in elderly subjects with the TT genotype. 20,21 Furthermore, we suggested that the association of the CC genotype with CRP was consistent with previous reports describing the association of the genotype with cardiac structures and atherosclerosis as discussed above, 17,34 whereas some apparent contradictory associations between the genotype and atherosclerosis, including cardiac structure and coronary artery diseases, have been shown in previous studies. 36,37 As the associations of the genotype with BP and atherosclerosis are still uncertain, these differences could be explained in part by the allelic distribution or sodium intake related to ethnicity, elimination of subjects under antihypertensive drug treatment or insufficient sample size.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] In addition, our results were not consistent with previous reports indicating that BP elevation was sensitive in elderly subjects with the TT genotype. 20,21 Furthermore, we suggested that the association of the CC genotype with CRP was consistent with previous reports describing the association of the genotype with cardiac structures and atherosclerosis as discussed above, 17,34 whereas some apparent contradictory associations between the genotype and atherosclerosis, including cardiac structure and coronary artery diseases, have been shown in previous studies. 36,37 As the associations of the genotype with BP and atherosclerosis are still uncertain, these differences could be explained in part by the allelic distribution or sodium intake related to ethnicity, elimination of subjects under antihypertensive drug treatment or insufficient sample size.…”
Section: Discussionsupporting
confidence: 92%
“…20 The other is the observation, in the elderly population, of a significantly higher systolic BP in subjects with the TT genotype. 21 These results suggest that the relationship between BP and the polymorphism may be affected by age.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…14 Non-hypertensive subjects, carriers of the T allele or TT genotype have high plasma aldosterone levels 15,16 and TT homozygotes show augmented systolic blood pressure with increasing age. 17 The studies on the association of this CYP11B2 gene polymorphism with gestational hypertension or preeclampsia are scant and remain controversial. Vasconcelos et al 18 did not find a significant association between the -344C/T polymorphism and gestational hypertension or preeclampsia, whereas Escher et al 19 found that the -344C/T genotype is increased, and the -344T/T genotype distribution is lower in the preeclamptic women as compared with normal pregnant women.…”
Section: Introductionmentioning
confidence: 99%
“…4 C-344T genotype was associated with systolic blood pressure and aldosterone to renin ratio in 437 elderly subjects. 5 Following oral sodium load TT and CT hypertensives exhibited greater suppression of serum aldosterone than CC hypertensives. 6 These studies suggest complex gene-environment interactions influence CYP11B2 gene expression, which may explain some of the contradictory associations reported in the literature.…”
mentioning
confidence: 95%